(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
The power chimney tower is one of modern promised energy which may be developed by low losses, simple and has high facilities. In this paper, many parameters were studied for prediction of system operation. Velocity distribution is the important parameter which gives the first prediction to put the position of erection of power turbine, made or not. The numerical analysis was presented by using GAMBIT and FLUENT 6.3 to predict that high velocity at the expansion of chimney near the solar collector place. This position is very suitable for promoting and building the power turbine since the velocity range was between (33 - 54 m/s) for different solar flux 200W/m2, 400W/m2, 600W/m2 and 800W/m2. So, the other factors, temperature and pressure were studied to coincide with previous papers in this field.